2016
DOI: 10.4178/epih.e2016011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic peripheral neuropathy class prediction by multicategory support vector machine model: a cross-sectional study

Abstract: OBJECTIVESDiabetes is increasing in worldwide prevalence, toward epidemic levels. Diabetic neuropathy, one of the most common complications of diabetes mellitus, is a serious condition that can lead to amputation. This study used a multicategory support vector machine (MSVM) to predict diabetic peripheral neuropathy severity classified into four categories using patients’ demographic characteristics and clinical features.METHODSIn this study, the data were collected at the Diabetes Center of Hamadan in Iran. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…It was not our goal for this model to be used for individual level patient care. Our model was trained on data from over 1.5 million patients from Ontario, which is among one of the most diverse populations in the world and, to our knowledge, one of the largest prediction modelling studies that takes into account multiple types of diabetes complications [22][23][24][25][26][27][28][29][30][31][32][33][34][51][52][53] . Our model was also wellcalibrated and showed good discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not our goal for this model to be used for individual level patient care. Our model was trained on data from over 1.5 million patients from Ontario, which is among one of the most diverse populations in the world and, to our knowledge, one of the largest prediction modelling studies that takes into account multiple types of diabetes complications [22][23][24][25][26][27][28][29][30][31][32][33][34][51][52][53] . Our model was also wellcalibrated and showed good discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Many prognostic models have been developed for diabetes complications in the clinical setting [22][23][24] , including more recent applications of machine learning approaches [25][26][27][28][29][30][31][32][33][34] . These models generally have made use of rich suites of features (e.g., body mass index, smoking status, biomarkers ranging from commonly ordered lipids to extensive genetic panels) extracted from electronic medical records (EMRs) 25,27,[31][32][33] or clinical trials 28,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this research aims to propose a DSPN severity classifier using the ANFIS algorithm to enhance the diagnosis facility for DSPN patients by early, accurate and reproducible screening and stratification of DSPN. In the literature, the Fuzzy Inference System (FIS) and support vector machine (SVM) algorithms have been introduced for detecting and classifying the severity of DSPN [20][21][22][23]. DSPN onset is insidious and progresses differently for every patient which makes it exhibits non-linear characteristics.…”
Section: ) Emg Based Dspn Severity Stratification Using Anfis Modelmentioning
confidence: 99%
“…Researchers using the fuzzy system for classification of the severity of DSPN have to design non-linear characteristics of DSPN through the IF-THEN rules which leave a chance of human error and reliant on expert knowledge, thus its accuracy is questionable. On the other hand, Kazemi et al [23] have identified different levels of DPN severity by using multicategory SVM (MSVM) and considered the neuropathy disability score (NDS) as the input of their MSVM classifier. However, the accuracy of their system was only 76%.…”
Section: ) Emg Based Dspn Severity Stratification Using Anfis Modelmentioning
confidence: 99%
See 1 more Smart Citation